Prevention in dangerous industries: does safety certification prevent tree-faller injuries? - Christopher B McLeod; Daniel Sarkany; Hugh Davies; Kevin Lyons; Mieke Koehoorn (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The aim of this study was to evaluate if safety certification reduces the risk of work injury among experienced manual tree-fallers. METHODS: This study used a retrospective cohort study design. Experienced manual tree-fallers employed in the Canadian province of British Columbia (N=3251) between 2003-2008 were enumerated from a mandatory faller registry. Registry records with demographic and certification data were linked to workers' compensation claims for injury outcomes. Data were analyzed using discrete time survival analysis over a two-year period, centered on certification date with pre- and post-certification demarcated into four three-month periods. Models were adjusted for demographic, occupation/industry, previous injury, and seasonal/temporal effects. RESULTS: The relative risk (RR) of work injury during the post certification periods were elevated in comparison to the pre-certification reference period, but the 95% confidence intervals included "1" for all estimates by the end of follow-up, suggesting no statistically significant increased risk of injury. Results were consistent across different outcome measures of acute injury (ie, fracture or amputations) (N=186), musculoskeletal injury (ie, back strain) (N=137), and serious injury claims (ie, long duration, high cost and/or fatal) (N=155). CONCLUSION: Certification did not reduce the risk of work injury among experienced tree-fallers in the province of British Columbia. Non-statistically significant increases in the observed risk of work injury in the months immediately following certification may be attributable to an intervention effect or a methodological limitation related to a lack of individual-level, time-at-risk exposure data.